The Uniqueness and Attractiveness of the Bima Language Linguistically - Adawiyah, Rabiyatul (e-Journal of Linguistics, 2021)
This study aims to determine the uniqueness and attractiveness of the Bima language linguistically, this is based on the fact that each regional language experiences its own characteristics. The research method used is qualitative with oral speech data sources, written data and language intuition. The research sample was in Lere Village, Parado District, Bima Regency, West Nusa Tenggara. Results From the study it was found that the Bima language did not have a final consonant in every word, all words in Bima ended with a vowel, even at the beginning of the word using vowels and there were additions or changes to the phonemes in the word. In addition to this, there is the elimination of the final consonant in a name, there are clusters (double consonants) at the beginning of the word. It was also found that words that have the same phoneme have different meanings in Indonesian by adding an apostrophe before the letters b or d. There is a phonemic relationship between nasal consonants in vocabulary. There are phonemes / consonant vocabulary that are interconnected in terms of meaning. Finally, for the clotting pattern in Bima, there are four syllable patterns, namely the (V), (KV), (KVK), and (1/2 KV) patterns. Consonants are not found in the closing syllables so that Bima is classified as a vocal language.